Challenges and Barriers to Providing Primary Care to Children of South Asian Origin: Pediatricians' Perspectives. (July 2023) - Ramachandran, Usha; Mahajan, Kaavya; Shah, Aashiki; Ghoshal, Bishakha; Khurshid, Afrida; Desilva, Nilifa; Shiriti, Margia; Patel, Nolan; Gaur, Sunanda; Karasz, Alison
South Asian (SA) Americans have a high risk of metabolic and cardiovascular disease. Prevention efforts should start in childhood and should be culturally appropriate. We sought to understand the challenges and barriers that pediatricians face in providing care for SA children to inform professional education on culturally effective care. Qualitative interviews were conducted with a diverse sample (N = 17) of pediatricians. Challenges reported included feeding problems, inadequate physical activity, and mental health concerns. Communication barriers included parents' anxiety around feeding, influence of grandparents, stigma around mental health, and cultural communication gaps. Effective strategies included clear communication, a gradual approach, ensuring buy-in from grandparents, greater attention to family history, and improved cultural knowledge in pediatrician. Addressing feeding problems was the most mentioned challenge, which is especially concerning given the high chronic disease risk in SAs. Education on culturally appropriate strategies can equip pediatricians to effectively counsel SA families to address these risks.